Analisis Desan dan Masyarakat Hukum Adat dalam Kerangka Hukum Nasional - Wa Ode Zamrud (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2021)
The research objective is to examine the perspective of the relationship between village and customaty law. This study uses doctrinal research with a philosophical approach and statutory regulations. This research examines the existence of a village which is part of the customary law community and customary law which has a strong relationship with the customary law community. Various references related to villages and various regulations made by the government regarding villages have placed the village as a basic power base and the forefront in maintaining local original values. In the structure of reality, the Indonesian nation has placed these values as one of the foundations for the development of Indonesian society. The basic paradigm of village and customary law is a connected community life, because the human values that are built in the village community are the values of customary law which are believed to be the basic principles for the development of a national cultural culture that is multiculturalism and pluralism. This study shows that village and customary law are an integrated unit in the life system of Indonesian society, so that legitimacy for villages and customary law communities is a characteristic and characteristic of local values that are built simultaneously.